Strategies for Fostering Nationalism through Buya Hamka's Sufism Educational Lens in the Digital Era - Firnando, Hero Gefthi (Teosofia: Indonesian Journal of Islamic Mysticism, 2024)
This study examines how Buya Hamka's Sufism education can foster the spirit of nationalism in the digital era. This study employs the phenomenological hermeneutic and content analysis approaches to extract and analyze Buya Hamka's views on spiritual intelligence and its role in fostering social purity. The findings reveal strategies from Buya Hamka to promote nationalism in the digital age by incorporating Sufism principles and practices into the educational framework. Hamka considers Sufism a unifying force capable of transcending divisions based on ethnicity and region. Sufism provides a common ground for Indonesians of various backgrounds to unite under a shared Islamic identity. Further, he argues the significance of Islam's inner and spiritual dimensions, such as spiritual discipline, as integral components of Islamic education. Education should stress elevating cognitive intelligence and nurture qualities such as compassion, humility, and integrity. In Hamka's view, Islamic education combines traditional Islamic teachings, Sufism principles, and a commitment to developing a strong national character.Contribution: This study provides a new perspective on education promoted by Buya Hamka to shape national identity in the digital era. Hamka insists on character building, cognitive and spiritual intelligence, and building nationalism character in Islamic education.